Penerapan Arsitektur Ekologi pada Bangunan Kamikatsu Zero Waste Center di Jepang - Tarra, Bintang Mahendra; Elviana, Eva (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Since 1990, the community of Kamikatsu, Japan, has recognized the negative environmental and resource impacts of burning waste, leading them to adopt a zero waste culture and declare themselves the first zero waste city in Japan in 2003. The Kamikatsu Zero Waste Center exemplifies the successful application of ecological architecture principles, responding to local climate conditions, creating energy efficiency, and integrating with the community's zero waste culture. This study aims to identify the success of the Kamikatsu Zero Waste Center in creating an ecological and sustainable community-based public space. The research method used is deductive, reviewing the general concept of ecological architecture and specifically examining its implementation in the Kamikatsu Zero Waste Center building. The findings demonstrate how the Kamikatsu Zero Waste Center addresses relevant issues through ecological architecture principles, such as building form and insulation in response to climate conditions, building openings for sunlight needs, and the use of local resources and recycled materials.